Flood Risk Assessment using Remote Sensing Techniques and Hydraulic Modelling in Khlong Bang Saphan Yai River Basin, Prachuap Khiri Khan Province - Seechana, Siriwat; Soytong, Phattraporn; Chen, Xiaoling; Lu, Jianzhong; Charoenjit, Kitsanai; Phodee, Pattama (Burapha Science Journal, 2026)
The Khlong Bang Saphan Yai River Basin is important in agriculture in Prachuap Khiri Khan Province. In 2018, there was a flood that affected several areas throughout the basin due to many days of heavy rainfall, resulting in high water levels in the Khlong Bang Saphan Yai River and overflows. Another factor is the high sea level which water could not drain into the sea and caused surface runoffs and floodplains in many areas. This study aims to determine the application of hydraulic modelling (HEC-RAS) integrated with remote sensing techniques to assess flood risk area in the Khlong Bang Saphan Yai River Basin. This study used Manning’s roughness coefficient (n) of 0.045 for both riverbanks and 0.050 for the channel. The HEC-RAS calibration and validation indicated a good agreement with observed daily discharge data during the periods of 2018 and 2019. Calibration results showed the Coefficient of determination (R2) value of 0.914 and the Nash-Sutcliffe coefficient of efficiency (NSE) value of 0.861. Validation results showed the R2 value was 0.822 and the NSE value was 0.634. The result of HEC-RAS simulation found that the maximum flow rate value of 127.17 m3/s and the maximum water level value of 9.08 m. MSL at the downstream gauging. In addition, the study of the validation assessment of the flood inundation from the model simulation was performed in comparison to the flooded extent derived from remote sensing techniques, the result showed overlapping of the flooded area of 0.22 km2 (17.5%). It covered four sub-districts, namely Ron Thong, Thong Mongkhon, Kamnoet Nopphakhun, and Phong Prasat in Bang Saphan Yai District, Prachuap Khiri Khan Province.